Implementasi Kriptografi Triple Des Dan Blowfish Pada Pengamanan File Multimedia Video - Aldi Wahyudi; Sumi Khairani; Dharmawati (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
Sending a message, data and information are very important and requires a high level of security. Developing of information technology is so rapid where everyone will find it is easy to get a message, data and information, especially video. Video is one of the multimedia content often uses. Maintaining the confidentiality of the video is important so that unauthorized people cannot see the message contained in the video. One of the methods used to secure video is using the triple des and blowfish algorithms, both of these algorithms are cryptographic methods that use the concept of block cipher and symmetric cryptography. These two algorithms are used as a reference in making encryption and decryption software for video files and analyzing the performance of existing security systems, and implementing them by testing and measuring the system, in terms of processing time for video files encryption and decryption. The application designed by using Visual Basic 2010 which is a programming language based on OOP (Object Oriented Programming) that utilizes .NET technology which is used to create applications in a Windows-based work environment. This application is expected to be able to accept the implementation of triple des and blowfish cryptography in securing multimedia video files properly and carry out the encryption and decryption process according to the algorithm